Inhibitory effects of selected phenolic acids on the oscillations of the Briggs-Rauscher reaction - Džomba, Emina; Gojak-Salimović, Sabina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Phenolic acids are secondary metabolites of aromatic plant that possess prominent antioxidant activity. When an antioxidant is added to an active oscillating Briggs-Rauscher reaction mixture, there is an immediate cessation of the oscillations, an inhibition time that linearly depends on the concentration of the antioxidant added, and a subsequent regeneration of oscillations. In this study, the effects of concentration of the ethanol solutions of selected phenolic acids (gallic, caffeic, chlorogenic, rosmarinic, p-coumaric and m-coumaric acids) on the oscillatory system Briggs-Rauscher reaction were investigated. The reaction was performed in a constantly stirred reactor, with accurately defined concentrations of reactants, at constant temperature of 25°C. Flow oscillations in the Briggs-Rauscher reaction mixture were monitored as a change in potential between the platinum electrode and silver/silver chloride reference electrode. Relative antioxidant activities of phenolic acids were determined in three ways on the basis of inhibition times. The obtained results showed that the gallic and p-coumaric acids have much less antioxidant activity than the caffeic, chlorogenic and rosmarinic acids. The ability to inhibit oscillations of the Briggs-Rauscher reaction mixture is not showed for m-coumaric acid.